2013
DOI: 10.1093/mnras/stt751
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-line region gas kinematics of 24 264 optically selected AGN: the radio connection

Abstract: Using a sample of 24264 optically selected AGNs from the SDSS DR7 database, we characterise how the profile of the [O III]λ5007 emission line relates to bolometric luminosity (L AGN ), Eddington ratio, radio loudness, radio luminosity (L 1.4 GHz ) and optical class (i.e., broad/narrow line Seyfert 1, Type 2) to determine what drives the kinematics of this kpcscale line emitting gas. Firstly, we use spectral stacking to characterise how the average [O III]λ5007 profile changes as function of these five variable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
456
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(503 citation statements)
references
References 67 publications
46
456
1
Order By: Relevance
“…We found that the objects for which we detect a broad component have FWHM larger than the average value observed in SDSS Type 2 AGN samples at similar observed [OIII] luminosity (Mullaney et al 2013;Greene et al 2011, see pinkish-grey and green points in Fig. 7).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We found that the objects for which we detect a broad component have FWHM larger than the average value observed in SDSS Type 2 AGN samples at similar observed [OIII] luminosity (Mullaney et al 2013;Greene et al 2011, see pinkish-grey and green points in Fig. 7).…”
Section: Discussionsupporting
confidence: 62%
“…Mullaney et al (2013) presented the analysis from a multicomponent (allowing for the presence of a broad component) line fit of the [OIII]5007 line in the SDSS population. In the lower panel of Fig.…”
Section: Type 2 Agn Samplesmentioning
confidence: 99%
“…Our observations of the "Teacup" AGN shed some light on the observed correlation between radio luminosity and the ionized gas kinematics (i.e., outflow velocities) seen in radio-quiet AGN (Mullaney et al 2013;). The radio emission in this radio-quiet AGN is tracing both a ≈1 kpc highvelocity outflow and ≈10-12 kpc radio bubbles that are likely to both be AGN driven.…”
Section: Discussionmentioning
confidence: 60%
“…Using the Sloan Digital Sky Survey (SDSS) spectrum, Reyes et al (2008) and Mullaney et al (2013) independently identified this source as a type 2 ("obscured") AGN.…”
Section: J1430+1339: the "Teacup" Agnmentioning
confidence: 99%
“…On the other hand, there is plenty of evidence for massive outflows in ULIRGs (e.g., Rupke, Veilleux & Sanders 2002;Martin 2005Martin , 2006) but these are not connected directly with the post starburst phase of such systems. Obviously, there are thousands of AGNs that show some indication of outflow, such as the large SDSS type-II sample studied by Mullaney et al (2013) and the more detailed study of 16 of those by Harrison et al (2014). However, there is no direct link between these outflows and the specific evolutionary phase of E+A galaxies.…”
Section: Introductionmentioning
confidence: 99%